Analysing customer responses to migrate strategies in making retailing and CRM effective. (2016) - Gupta, Gaurav; Aggarwal, Himanshu
As the world is growing more and more competitive, the customer experience is becoming more important to the businesses. There is a need for appropriately aligned customer-centric strategy to maintain synchronisation between customers' expectations and services provided to them. This can be achieved through customer relationship management (CRM). CRM is a comprehensive strategy and a process of acquiring, retaining, and partnering with selective customers to create superior value for the business by using customer knowledge. A business strategy needs to be designed that reduces the cost by increasing customer loyalty and business profitability. The objective of the paper is to point out the relevant factors that may be helpful to the retailers in increasing their profit, sales and building long-term relationships with the customers. The factors have been extracted from the pool of factors that are surveyed from the customers at the shopping mall, marts and supermarket. The findings may help the retailers in developing their strategies during sales, promotions, marketing, business and customer build ups and maintaining log-term relationships with the customers.